Expression analysis of LlMYC2 during the development of microbulbs in Lilium lancifolium(LlMYC2在卷丹微鳞茎发育过程中的表达分析) - 桑倩姿(SANG Qianzi); 陈妍竹(CHEN Yanzhu); 潘文强(PAN Wenqiang); 张铭芳(ZHANG Mingfang); 杨凤萍(YANG Fengping); 张婷(ZHANG Ting); 刘仲旭(LIU Zhongxu); 杜运鹏(DU Yunpeng); 曹丽(CAO Li) (浙江大学学报. 农业与生命科学版)
MYC2 (myelocytomatosis protein 2) transcription factor is a member of the basic helix-loop-helix (bHLH) transcription factor family and is a key regulator of the jasmonate signaling pathway, which is involved in plant growth, development, and defense processes. In this study, the LlMYC2 gene of Lilium lancifolium was cloned, and the function and expression of this gene were analyzed to preliminarily explore the mechanism by which the LlMYC2 gene regulates the expansion ofthe microbulbs (bulblets and bulbils) in Lilium lancifolium. The results showed that the LlMYC2 gene is 2 148 bp in length, encodes 715 amino acids, has a molecular mass of 77.745 kDa, contains a typical MYC domain, and lacks the transmembrane domain. Phylogenetic tree analysis revealed that the LlMYC2 protein was the most closely related to the MYC2 proteins of Lilium regale and Lilium hybrid division Ⅶ. Subcellular localization results showed that LlMYC2 was a nucleus localized protein. Real time fluorogenic quantitative polymerase chain reaction (qRT-PCR) results showed that LlMYC2 was expressed in different tissues of Lilium lancifolium, with the highest expression level in the leaves, followed by the ovary, mature bulbils and mature bulblets. The expression level of LlMYC2 showed two distinct upregulation trends in the growth and development of microbulbs. Gene function verification results showed that after silencing LlMYC2 in Lilium lancifolium microbulbs, the expansion of bulblets and bulbils was inhibited. Treatment of mature bulbils with methyl jasmonate (MeJA) and its biosynthesis inhibitor salicylic acid hydroxamic acid (SHAM) affected the expression of LlMYC2. In summary, LlMYC2 is involved in the development of Lilium lancifolium microbulbs and the expansion of Lilium lancifolium microbulbs. . MYC2（myelocytomatosis protein 2）转录因子是碱性螺旋-环-螺旋（basic helix-loop-helix, bHLH）转录因子家族成员，是茉莉酸信号通路的关键调节因子，参与调控植物生长发育和防御过程。本研究通过克隆卷丹（Lilium lancifolium）LlMYC2基因，对其基因功能和表达进行分析，以初步探究LlMYC2基因调节卷丹微鳞茎（小鳞茎和珠芽）膨大的作用机制。结果表明：LlMYC2基因编码区全长2 148 bp，编码715个氨基酸，蛋白质分子量为77.745 kDa，含1个典型的MYC结构域，无跨膜结构域。系统进化树分析发现，LlMYC2蛋白与岷江百合（Lilium regale）和杂交百合（Lilium hybrids division Ⅶ）的MYC2蛋白亲缘关系最近。亚细胞定位结果显示，LlMYC2定位于细胞核中。实时荧光定量聚合酶链反应结果表明，LlMYC2在卷丹不同组织中均有表达，其中在叶片中表达量最高，在子房、成熟珠芽和成熟小鳞茎中的表达量次之；LlMYC2表达量在微鳞茎生长发育过程中有2次明显上调。基因功能验证结果表明，沉默卷丹微鳞茎中LlMYC2后，其珠芽和小鳞茎的膨大均受到抑制。茉莉酸甲酯及其生物合成抑制剂水杨酸羟肟酸处理成熟珠芽时，会影响LlMYC2的表达。综上所述，LlMYC2参与卷丹微鳞茎的发育，同时促进卷丹微鳞茎的膨大。